2015
DOI: 10.1007/s00246-015-1201-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Children with Congenital Heart Diseases: A Multicenter Controlled Cross-Sectional Study

Abstract: To assess the health-related quality of life (QoL) in children with congenital heart diseases (CHD) with a validated questionnaire in comparison with control children. We prospectively recruited 282 children with CHD aged from 8 to 18 years in two tertiary care centers (France and Belgium) and 180 same-age controls in randomly selected French schools. Children's QoL was self-reported with the KIDSCREEN-52 questionnaire and reported by parents with the KIDSCREEN-27. QoL scores of each dimension were compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 53 publications
8
95
0
2
Order By: Relevance
“…These results are consistent with previous results from smaller or non-controlled cohorts from the literature,28–31 where, to our knowledge, no multivariate analysis had been performed to identify the clinical determinants of VO 2max in cardiac children. We recently emphasised the impact of these clinical severity variables on the quality of life of children with CHD 6. In paediatric cardiology, CPET could therefore contribute to assess disease severity and its impact on daily living, as in adults with CHD 4 32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previous results from smaller or non-controlled cohorts from the literature,28–31 where, to our knowledge, no multivariate analysis had been performed to identify the clinical determinants of VO 2max in cardiac children. We recently emphasised the impact of these clinical severity variables on the quality of life of children with CHD 6. In paediatric cardiology, CPET could therefore contribute to assess disease severity and its impact on daily living, as in adults with CHD 4 32…”
Section: Discussionmentioning
confidence: 99%
“…Yet there is a growing number of children and adolescents living with CHD,5 and their increase in life expectancy should also lead to a better quality of life. This includes the ability to engage in normal physical activity, which is a main quality of life parameter 6. Indeed, we recently pointed out a correlation between quality of life and VO 2max in a large cohort of children with CHD 7.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the quality of life scores were not significantly higher in the sophrology group than in the control group, at the end of the hospitalization. Usually, patient reported outcomes require larger cohorts to be statistically modified, as reported in our previous quality of life studies …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, despite these great advances, psychological trauma is not uncommon for CHD survivors . Moreover, we recently showed that the quality of life was impacted by the number of invasive procedures and the level of anxiety in the CHD population …”
Section: Introductionmentioning
confidence: 99%
“…Assessing the level of anxiety in parents of children with CHD is of interest but remains time consuming for medical staff and patients, especially when using the existing instruments. Indeed, the 31‐item perinatal anxiety screening scale (PASS) and the 21‐item depression, anxiety and stress scale (DASS 21) both require a minimum of 20 minutes to be completed . These specialized anxiety scales have as such mainly been used in clinical research but only rarely on a routine basis .…”
Section: Introductionmentioning
confidence: 99%